2005
DOI: 10.1093/jnci/dji315
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase III Study of Doxorubicin Versus Cisplatin/Interferon α-2b/Doxorubicin/Fluorouracil (PIAF) Combination Chemotherapy for Unresectable Hepatocellular Carcinoma

Abstract: Although patients on PIAF had a higher overall response rate and better survival than patients on doxorubicin, the differences were not statistically significant. PIAF was also associated with increased treatment-related toxicity. The prognosis of patients with unresectable HCC remains poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
408
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(420 citation statements)
references
References 30 publications
5
408
2
5
Order By: Relevance
“…Many small-scale trials of combining MTT with cytotoxic chemotherapy have been reported [385][386][387][388][389]. However, the treatment efficacy in terms of tumor response rate and patient survival were similar to those reported for the cytotoxic regimens alone (Table 3) [372,[375][376][377][378][379][380][381][382]. A second approach is to combine MTT targeting different molecular pathways.…”
Section: Future Directionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Many small-scale trials of combining MTT with cytotoxic chemotherapy have been reported [385][386][387][388][389]. However, the treatment efficacy in terms of tumor response rate and patient survival were similar to those reported for the cytotoxic regimens alone (Table 3) [372,[375][376][377][378][379][380][381][382]. A second approach is to combine MTT targeting different molecular pathways.…”
Section: Future Directionsmentioning
confidence: 83%
“…Objective tumor response rate to single-agent cytotoxic therapies is usually less than 10%, and no survival benefit has been observed [372][373][374][375][376]. An earlier randomized trial comparing doxorubicin, 60-75 mg/m 2 every 3 weeks, with no treatment indicated a borderline improvement in overall survival (10.6 vs. 7.5 weeks) for patients who received doxorubicin [377].…”
Section: Cytotoxic Therapy: Single Agent and Combinationmentioning
confidence: 99%
“…By this time, the HCC xenografts reached the size of f100 mg. The dose of doxorubicin was f60% of the dose used in human [60 mg/m 2 or 1.6 mg/kg (12)]. Growth of established xenografts was monitored at least twice weekly, and tumor volume was calculated as described (31).…”
Section: Methodsmentioning
confidence: 99%
“…Recent large phase III studies have shown a 4% to 10.5% response rate in HCC treated with doxorubicin in the control group (11,12). Overall response rate, but not overall survival, was doubled when doxorubicin was given in combination with cisplatin, IFN, and 5-fluorouracil (12).…”
Section: Introductionmentioning
confidence: 99%
“…Hep3B cells (80% confluent) were exposed to 100 lM rosiglitazone for various times (3,8,12, or 24 hours). The PPARc/DNA binding activity in nuclear extract was measured using an enzyme-linked immunosorbent assay (ELISA)-based assay (Cayman Chemical, Ann Arbor, Mich).…”
Section: Pparc Binding Activity Assaymentioning
confidence: 99%